Acute Stress-Induced Epigenetic Modulations and Their Potential Protective Role Toward Depression - Rusconi, Francesco; Battaglioli, Elena (Frontiers in Molecular Neuroscience, 2018)
Psychiatric disorders entail maladaptive processes impairing individuals’ ability to appropriately interface with environment. Among them, depression is characterized by diverse debilitating symptoms including hopelessness and anhedonia, dramatically impacting the propensity to live a social and active life and seriously affecting working capability. Relevantly, besides genetic predisposition, foremost risk factors are stress-related, such as experiencing chronic psychosocial stress –including bullying, mobbing and abuse–, and undergoing economic crisis or chronic illnesses. In the last few years the field of epigenetics promised to understand core mechanisms of gene-environment crosstalk, contributing to get into pathogenic processes of many disorders highly influenced by stressful life conditions. However, still very little is known about mechanisms that tune gene expression to adapt to the external milieu. In this Perspective we discuss a set of protective, functionally convergent epigenetic processes induced by acute stress in the rodent hippocampus and devoted to the negative modulation of stress-induced Immediate Early Genes (IEGs) transcription, hindering stress-driven morphostructural modifications of corticolimbic circuitry. We also suggest that chronic stress damaging protective epigenetic mechanisms, could bias the functional trajectory of stress-induced neuronal morphostructural modification from adaptive to maladaptive, contributing to the onset of depression in vulnerable individuals. A better understanding of the epigenetic response to stress will be pivotal to new avenues of therapeutic intervention devoted to treat depression, especially in light of limited efficacy of available antidepressant drugs.